Multicenter Epidemiologic Study on Hepatocellular Carcinoma in Turkey - (:unkn) unknown (ASIAN PACIFIC ORGANIZATION CANCER PREVENTION, 2014)
Background: Hepatocellular cancer (HCC) is one of the important health problems in Turkey, being very common and highly lethal. The aim of this study was to determine clinical, demographic features and risk factors. Materials and Methods: Nine hundred and sixth-three patients with HCC from 13 cities in Turkey were included in this study. Results: Only 205 (21%) of the 963 patients were women, with a male: female predominance of 4.8:1 and a median age of 61 years. The etiologic risk factors for HCC were hepatitis B in 555 patients (57.6%), 453 (81%) in men, and 102 (19%) in women, again with male predominance, hepatitis C in 159 (16.5%), (14.9% and 22.4%, with a higher incidence in women), and chronic alcohol abuse (more than ten years) in 137 (14.2%) (16.8% and 4.9%, higher in males). The Child-Pugh score paralleled with advanced disease stage amd also a high level of AFP. Conclusions: According to our findings the viral etiology (hepatitis B and hepatitis C infections) in the Turkish population was the most important factor in HCC development, with alcohol abuse as the third risk factor. The Child-Pugh classification and AFP levels were determined to be important prognostic factors in HCC patients.
Keywords: Hepatocellular carcinoma; etiologic factors; alpha-fetoprotein; Turkey; PROGNOSTIC FEATURES; VIRAL-HEPATITIS; ALPHA-FETOPROTEIN; RISK-FACTORS; SURVIVAL; CANCER